Imaging of skin birefringence for human scar assessment using polarization-sensitive optical coherence tomography aided by vascular masking - Gong, P.; Chin, L.; Es'haghian, S.; Liew, Y.M.; Wood, F.M.; Sampson, D.D.; McLaughlin, R.A. (International Society for Optical Engineering (SPIE), 2014)
We demonstrate the in vivo assessment of human scars by parametric imaging of birefringence using polarization-sensitive optical coherence tomography (PS-OCT). Such in vivo assessment is subject to artifacts in the detected birefringence caused by scattering from blood vessels. To reduce these artifacts, we preprocessed the PS-OCT data using a vascular masking technique. The birefringence of the remaining tissue regions was then automatically quantified. Results from the scars and contralateral or adjacent normal skin of 13 patients show a correspondence of birefringence with scar type: the ratio of birefringence of hypertrophic scars to corresponding normal skin is 2.2 +/- 0.2 (mean +/- standard deviation), while the ratio of birefringence of normotrophic scars to normal skin is 1.1 +/- 0.4. This method represents a new clinically applicable means for objective, quantitative human scar assessment. (C) 2014 Society of Photo-Optical Instrumentation Engineers (SPIE)